2021
DOI: 10.1097/ico.0000000000002698
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Donor Insertion and Unfolding in Descemet Membrane Endothelial Keratoplasty

Abstract: To describe a novel technique for insertion and unfolding of donor Descemet membrane (DM) scroll during DM endothelial keratoplasty (DMEK).Methods: DMEK was performed in 20 eyes. The donor DM scroll was loaded into a glass injector, and the fluid column was manipulated to achieve a double scroll configuration. After performing DM stripping and inferior iridectomy, an anterior chamber (AC) maintainer was placed in position. The glass injector was inserted into the AC and the tip rotated to ensure correct orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…A single clinical outcome study using the fluid column manipulation technique reported an 85% success rate for achieving the double-scroll conformation, shorter duration of unfolding in double-scrolled grafts compared with single-scrolled grafts, and a low 6- and 12-month ECL (16.7% and 24.9%, respectively) in double-scroll graft recipients. 13 Although this study suggests that use of double-scrolled tissue results in promising clinical outcomes, it was limited by its low sample size and that it reported results of a single, experienced DMEK surgeon. Our study demonstrates that a double-scroll formation technique can be used on younger, tightly rolled, single-scrolled grafts without introduction of additional ECL at the time of processing.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A single clinical outcome study using the fluid column manipulation technique reported an 85% success rate for achieving the double-scroll conformation, shorter duration of unfolding in double-scrolled grafts compared with single-scrolled grafts, and a low 6- and 12-month ECL (16.7% and 24.9%, respectively) in double-scroll graft recipients. 13 Although this study suggests that use of double-scrolled tissue results in promising clinical outcomes, it was limited by its low sample size and that it reported results of a single, experienced DMEK surgeon. Our study demonstrates that a double-scroll formation technique can be used on younger, tightly rolled, single-scrolled grafts without introduction of additional ECL at the time of processing.…”
Section: Discussionmentioning
confidence: 93%
“…Veldman and Fogla have demonstrated that a double-scrolled DMEK graft can be formed from a single-scrolled graft inside the injector by manipulating the fluid column immediately before graft ejection into the anterior chamber. 12,13 However, no laboratory studies were presented to detail whether repeated manipulation of the DMEK graft within the fluid column and expulsion of a graft from an injector results in increased ECL. A single clinical outcome study using the fluid column manipulation technique reported an 85% success rate for achieving the double-scroll conformation, shorter duration of unfolding in double-scrolled grafts compared with single-scrolled grafts, and a low 6- and 12-month ECL (16.7% and 24.9%, respectively) in double-scroll graft recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search also revealed the use of viscoelastic for descemetorhexis. [ 40 41 ] The author also advised roughening of peripheral 2 mm of the bare stroma with the scraper to facilitate better graft adherence. [ 41 ] In cases with endoglide-assisted insertion of graft, a temporal scleral tunnel making is preferred with a nasal paracentesis for endoglide placement forceps to pull the graft into the anterior chamber.…”
Section: Surgical Steps Of Dmekmentioning
confidence: 99%
“…A novel technique of donor insertion described by Fogla et al . [ 40 ] uses a glass cartridge attached to the prefilled syringe. The cartridge is inserted into the AC and rotated to orient the graft in the desired orientation.…”
Section: Donor Insertion Techniques and Devicesmentioning
confidence: 99%